Thermal Properties and Moisture Content Analysis of Starch Fiber Filled Polyvinyl Alcohol-Polyvinyl Acetate (Pva-Pvac) Biofilm - Shahrul Nizam Salleh, Mohd; Rasit Ali, Roshafima; Farid Haikal Zainal, Muhammad (International Journal of Engineering and Technology, 2018)
This study aimed to determine the effect of starch fiber onto thermal properties of Polyvinyl Alcohol (PVA)-Polyvinyl Acetate (PVAc) blends. Starch fiber was used in this study as the reinforced filler. The starch fiber (SF) was prepared by extracting the potatoâ€™s peels. Prior to the preparation of biofilms, the PVA and PVAc were plasticized using glycerol and distilled water. The biofilm of SF-PVA-PVAc were produced using casting technique. A thermal analysis was conducted on the biofilms to investigate the thermal stability of the sample using Thermogravimetric Analysis (TGA). Besides the moisture content of the derive biofilm was also studied. It was found that biofilm with higher composition of SF (50wt%) noted the highest degradation temperature (Tdg) at 297oC. Conversely, biofilm with highest composition of SF recorded the lowest moisture content. This may be attributed to the content of fiber which predominated the matrix of biofilm.Â